2019
DOI: 10.1186/s42269-019-0115-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the benzo[a]anthracene biodegradation by animal bioassays

Abstract: Background: Benzo[a]anthracene (BAA), also known as "tetraphene" belongs to the polycyclic aromatic hydrocarbons (PAHs) which are considered as an important class of environmental genotoxins. The present work focused on the evaluation of the efficiency of the biodegradation of the BAA by Bacillus amyloliquefaciens using animal bioassays, which include micronucleus (MN) and DNA fragmentation as end point of genotoxicity of the resulting metabolites from BAA biodegradation. Results: B. amyloliquefaciens was expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In animal studies it has been found to be genotoxic, carcinogenic that induce skin, lungs, and liver tumors in the young mice after dermal application, absorption, subcutaneous and intraperitoneal injection. It was found to cause micronucleus and DNA fragmentation in mice [53].…”
Section: Benzo[a]anthracenementioning
confidence: 99%
“…In animal studies it has been found to be genotoxic, carcinogenic that induce skin, lungs, and liver tumors in the young mice after dermal application, absorption, subcutaneous and intraperitoneal injection. It was found to cause micronucleus and DNA fragmentation in mice [53].…”
Section: Benzo[a]anthracenementioning
confidence: 99%